2021
DOI: 10.1155/2021/6927025
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Carvedilol on Diabetic Neuropathy: An In Vitro Study

Abstract: Diabetic neuropathy serves as a major complication for diabetic patients across the world. The use of effective treatment is integral for reducing the health complications for diabetic patients. This study has evaluated the carvedilol potential neuroprotective effect on diabetic neuropathy. An in vitro model of diabetic neuropathy was used, including dorsal root ganglia (DRG) that were cultured from male adult mice C57BL. These were incubated for about twenty-four hours in high glucose (HG) media (45 mM). Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Consideration is mainly due to the fact that carvedilol is a nonselective β -blocker that selectively blocks the receptors along with the full range of B receptors [ 29 ]. At the same time, carvedilol is able to increase insulin sensitivity and improve lipid and glucose metabolism in general, which is related to the receptor blocker effect of carvedilol as well as elevating lipid oxidase activity and regulating disordered lipid and glucose metabolism [ 30 ]. Thus, carvedilol is effective in lowering blood pressure while having effects that are not found in other β -blockers, which improve insulin sensitivity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consideration is mainly due to the fact that carvedilol is a nonselective β -blocker that selectively blocks the receptors along with the full range of B receptors [ 29 ]. At the same time, carvedilol is able to increase insulin sensitivity and improve lipid and glucose metabolism in general, which is related to the receptor blocker effect of carvedilol as well as elevating lipid oxidase activity and regulating disordered lipid and glucose metabolism [ 30 ]. Thus, carvedilol is effective in lowering blood pressure while having effects that are not found in other β -blockers, which improve insulin sensitivity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to exhibit antioxidant activity (Pereira et al, 2011;Arab and El-Sawalhi, 2013;Yasar et al, 2013;Diogo et al, 2017) and prevent reduction of nerve conduction velocity (Cotter and Cameron, 1995). Most recently, carvedilol has been revealed by Magadmi et al (Magadmi et al, 2021) to display a neuroprotective effect in vitro in high glucose-induced neuronal damage on cultured dorsal root ganglia. Hence, this work has been extended to investigate in vivo the potential neuroprotective effect of carvedilol on STZ-induced DN in rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic peripheral neuropathy is presented as spontaneous pain and hyperalgesia due to hyperglycemia-induced sensory neuronal dysfunction [15,16]. A large and growing body of literature has indicated that hyperglycemia-induced oxidative stress and inflammation are key pathways in developing diabetic neuropathy [4].…”
Section: Discussionmentioning
confidence: 99%